Penggunaan Obat Off Label di Instalasi Rawat Inap Rumah Sakit Kahyangan - Happy Elda Murdiana (Jurnal Farmasi Indonesia, 2016)
Off label drug use is defined as prescriptions for indications or dosage form that did not pass the approval process asociations Food and Drug Administration (FDA). The main reason the off label use of the drug in pregnant women is to avoid complications such as premature birth problems womb, labor, pre-eclampsia and eclampsia or increase the capacity of postnatal adaptation that may occur for example, sepsis or respiratory distress. The purpose of this studywas to determine the type and percentage of drugs used off label installed hospital inpatient heavenly. The research method using the cross section for the retrieval of data from medical records and descriptive analysis. The results obtained was 9.8% lidocaine for perineal sewing anestesi therapy, 5.6% misoprostol for induction of labor and 8.5% issue of abortion, ondancetron 59.1% for the prophylaxis of nausea and vomiting due anestesi cesarean section, bupivacaine 59.1 % The FDA does not approve the use of spinal anestesia, analgesic ketorolax 59.1% cesarean surgery, dexamethasone 1.4% for fetal lung maturation has not been quite the month. So there were six kinds of off label drug used that all off label indications already mentioned above.